Spinal Osseous Epidural Arteriovenous Fistula with Multiple Small Arterial Feeders Converging to a Round Fistular Nidus as a Target of Venous Approach - Chul Suh, Dae; Gon Choi, Choong; Bo Sung, Kyu; Kim, Kwang-Kuk; Chul Rhim, Seung (American Journal of Neuroradiology, 2004)
Summary: We present two patients with spinal epidural arteriovenous fistulas involving the vertebral body recruiting dural and osseous branches as feeders. The fistulas, forming a round venous sac into which the multiple arterial feeders converge, were located near the round bony defect of the vertebral body, suggesting the osseous component of this vascular lesion. Transvenous coil embolization of the round venous sac results in near-total obliteration of the lesion, leading to symptomatic improvement.